2020
DOI: 10.1038/s41598-020-60104-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen sufficiency enhances thermal tolerance in habitat-forming kelp: implications for acclimation under thermal stress

Abstract: Local and global changes associated with anthropogenic activities are impacting marine and terrestrial ecosystems. Macroalgae, especially habitat-forming species like kelp, play critical roles in temperate coastal ecosystems. However, their abundance and distribution patterns have been negatively affected by warming in many regions around the globe. Along with global change, coastal ecosystems are also impacted by local drivers such as eutrophication. The interaction between global and local drivers might modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 115 publications
2
60
1
Order By: Relevance
“…The lack of phosphorus is accentuated in the stage of rapid multiplication. The mean element concentration value was significantly higher than the magnitude reported by [31]. The tropical macroalgae typical of environments with high concentrations of carbonate in sediments (0.07% vs 0.16% d. w).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The lack of phosphorus is accentuated in the stage of rapid multiplication. The mean element concentration value was significantly higher than the magnitude reported by [31]. The tropical macroalgae typical of environments with high concentrations of carbonate in sediments (0.07% vs 0.16% d. w).…”
Section: Discussioncontrasting
confidence: 60%
“…Temperature or lighting limitations are capable of uncoupling the tissue concentration of some nutrients from the growth rate [35] [36]. This phenomenon is capable of restricting net algal productivity [31].…”
Section: Discussionmentioning
confidence: 99%
“…The seaweed industry requires large quantities and high-quality seaweed raw material that exerts pressure on the existing natural seaweed resources. Aquaculture cultivation of seaweed has grown considerably since 2009 to meet product demand and to protect wild kelp beds that are still under threat from over-exploitation and climate change, which has caused increases in ocean water temperatures [ 251 ]. To produce high value products (HVP) from seaweed requires considerable cultivation control to retain quality biomass, not possible in offshore systems; therefore, onshore aquacultures have been proposed to fulfil this need [ 252 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally thought that Macrocystis tends to be a more cold-adapted species, and cannot survive at temperatures above 20 °C 53 , 63 . A recent study has shown that the optimum temperature (T opt ) for growth in adult’s individuals of Macrocystis is close to 16 °C, and temperature above T opt (i.e., at 24 °C) can negatively affect its physiological performance 104 . However, NO 3 − enrichment can modulate these responses, enhancing for example, their physiological thermal tolerance, ameliorating the negative impacts of sub-optimal temperatures 104 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that the optimum temperature (T opt ) for growth in adult’s individuals of Macrocystis is close to 16 °C, and temperature above T opt (i.e., at 24 °C) can negatively affect its physiological performance 104 . However, NO 3 − enrichment can modulate these responses, enhancing for example, their physiological thermal tolerance, ameliorating the negative impacts of sub-optimal temperatures 104 . Although we found that both populations were equally negatively affected by elevated temperatures, relative growth rates remained above 9% day −1 , which might be attributed to the non-limiting level of NO 3 − supplied during the experiments (> 5 µM).…”
Section: Discussionmentioning
confidence: 99%